Perspektif Jacques Lacan terhadap Fenomena Cyberbullying di Indonesia Menjelang Pemilu Tahun 2024 - Devitasari, Erliyana (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2023)
This article is the result of qualitative research through literature study and observation. The object studied in this article is the phenomenon of cyberbullying ahead of the 2024 general election in Indonesia. While the analysis process carried out uses the hermeneutic method with the perspective of Jacques Lacan's thought. Based on the research that has been done, it is found that: (1) Jacques Lacan is a post-modern philosopher who has successfully brought psychoanalytic studies into philosophical studies. Lacan developed the discourse of the unconscious in psychoanalytic thought by presenting his views on the stages of development of the Subject, namely the Real, the Imaginary, and the Symbolic. (2) The practice of cyberbullying ahead of the 2024 general election is carried out with the aim of bringing down individuals, groups, or groups that have different directions of political support. Various bullying vocabularies are used to identify and bring down different parties symbolically. (3) The phenomenon of cyberbullying approaching the 2024 political year shows the Subject's entrapment into the Symbolic. With various bullying vocabularies addressed to parties with different political support, the Subject is increasingly falling into the pit of castration (jouissance) which keeps him away from fulfilment and wholeness at the stage of the Real that he desires.